Spiritual and cultural links between Vallejo and Oscar Imaña - Salas Salas, Luzmán (Espergesia, 2015)
This paper attempts to demonstrate objectively the evidence of the close affective and cultural relationship between the Peruvian poets Cesar Vallejo and Oscar Imaña, both members of the historical artistic and literary group known as Grupo Norte, in the city of Trujillo, Peru. To highlight this intimate and fraternal rapprochement, in the present study we have considered entering letters from Vallejo addressed to Oscar Imaña, where vocatives, farewells, yearnings and cultural and personal concerns prove the close friendship between these two poets. In addition, through the analysis of some texts, some thematic and formal coincidences are shown between these authors e.g. topics of reproach, accusation, complaints to God; references to the rain, kissing, Jesus, among others.